2015
DOI: 10.1080/15435075.2014.968922
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of new solar air heater design

Abstract: The suitable design is the most important key to a cost-effective solar air heater. Although, there are many techniques that have been proposed to improve the solar air heaters' performance by means of different turbulence promoters, they cannot ensure a compromise between the cost and the effectiveness. The aim of this study is to find simple and tolerable solution to get rid of the inconvenience resulting from the widely adopted heat transfer enhancement techniques by providing an optimized solar air heater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…They have taken the initial design proposed in the reference [11]. The Computational Fluid Dynamic (CFD) model is validated by the results reported by Mahboub et al [11]. They observed that secondary vortex formation near the absorber wall increases the Nusselt number significantly.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…They have taken the initial design proposed in the reference [11]. The Computational Fluid Dynamic (CFD) model is validated by the results reported by Mahboub et al [11]. They observed that secondary vortex formation near the absorber wall increases the Nusselt number significantly.…”
Section: Introductionmentioning
confidence: 88%
“…Two years later; Singh et al [12] investigated numerically various curved solar air heater designs that shows significant enhancement of heat transfer and thermal efficiency. They have taken the initial design proposed in the reference [11]. The Computational Fluid Dynamic (CFD) model is validated by the results reported by Mahboub et al [11].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Convergence criteria have been considered of order 10 I• for energy equation and 10 I' order for the velocity component and the momentum equation. (Mahboub et al, 2016;Nivedita et al, 2017;Singh & Singh, 2018). However, in this present simulation Reynolds number (Re) and Dean number ( -) are in the range of 2209-6058 and 180-494, respectively which comes under turbulent range (Mahboub et al, 2016;Nivedita et al, 2017;Singh & Singh, 2018), hence turbulent flow model has been considered during the entire simulation run.…”
Section: Boundary Condition and Governing Equationsmentioning
confidence: 99%
“…al. (11) An energy and exergy study has been done Gupta D et al (2011) on a double pass flat plate solar air collector with and without porous medium embedded inside the lower channel of the collector. The obtained results show that employing porous medium can increase the thermal efficiency of the collector of more than 30%, while a second law analysis shows that the friction with the porous medium can also increase the pressure drop in the air.…”
Section: Introductionmentioning
confidence: 99%